Comparative evaluation of echocardiographic and morphometric characteristics of the rat heart left ventricle - E. O. Ionova; I. A. Miroshkina; A. V. Sorokina; S. A. Kryzhanovskii (Фармакокинетика и Фармакодинамика)
Purpose of the study. Comparative evaluation of echocardiographic and morphometric dimensions of the rat heart left ventricle. Materials and methods. The study included 10 outbred male rats weighing 160–180 g. The size of the heart left ventricle was assessed using echocardiography and morphometry. The measurements were carried out according to standard protocols. To perform morphometric measurements, hearts were stopped in systole with a lethal dose (1.0 mg/kg) of 0.025 % strophanthin K solution, and in diastole, by immersing the hearts in a chilled physiological solution (calcium-free medium). Results. It was shown that the systolic size of the left ventricle of the heart according to echocardiography is 1.79Ѓ}0.10 mm, and morphometry 1.64Ѓ}0.09 mm (p = 0,302); diastolic size of the left ventricle, respectively, 3.42Ѓ}0.16 mm and 3.66Ѓ}0.17 mm (р = 0,318). The detected discrepancies do not exceed 10 % and, apparently, are due to the fact that the physiological dimensions of the heart left ventricle are measured by a non-invasive echocardiographic method, and for morphometric measurements of the dimensions in the systole, the heart was stopped by injection of strophanthin K, which entails an overload of heart cells with Ca2+ ions and as a result, contracture of cardiomyocytes; post-mortem cardiac arrest in diastole, in a calcium-free environment, is accompanied by a loss of cardiac muscle tone and, therefore, dilatation of the left ventricle will naturally be greater than physiological. Conclusion. Noninvasive echocardiographic measurement of the size of the heart left ventricle fully reflects the actual size of the left ventricle of the rat heart (the difference does not exceed 10 %), i. e. echocardiographic measurements are valid.